2020
DOI: 10.1177/1745691619879167
|View full text |Cite
|
Sign up to set email alerts
|

Witnessing, Remembering, and Testifying: Why the Past Is Special for Human Beings

Abstract: The past is undeniably special for human beings. To a large extent, both individuals and collectives define themselves through history. Moreover, humans seem to have a special way of cognitively representing the past: episodic memory. As opposed to other ways of representing knowledge, remembering the past in episodic memory brings with it the ability to become a witness. Episodic memory allows us to determine what of our knowledge about the past comes from our own experience and thereby what parts of the past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 92 publications
1
12
0
Order By: Relevance
“…Future studies should therefore seek to establish a causal relationship between speaker accountability and statement believability not mediated by source claims. Nonetheless, the results presented here tie in with the idea that tracking where one’s own beliefs come from is not just important for epistemic reasons (e.g., Mahr & Csibra, 2018 ; 2020 ; Mahr et al, 2020 ). Instead, source information plays an important role when one wants to transmit those beliefs to others by allowing speakers to calibrate their conversational commitments.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Future studies should therefore seek to establish a causal relationship between speaker accountability and statement believability not mediated by source claims. Nonetheless, the results presented here tie in with the idea that tracking where one’s own beliefs come from is not just important for epistemic reasons (e.g., Mahr & Csibra, 2018 ; 2020 ; Mahr et al, 2020 ). Instead, source information plays an important role when one wants to transmit those beliefs to others by allowing speakers to calibrate their conversational commitments.…”
Section: Discussionsupporting
confidence: 80%
“…For example, modal expressions in English and German (such as must , presumably , maybe, definitely ) have an evidential interpretation (Degen et al, 2019 ). In fact, the role of source information in communication is so important that Mahr and Csibra ( 2018 ; 2020 ) have proposed that it contributed to shaping the evolution of episodic memory to serve as a form of source memory in humans. Mahr and Csibra explicitly argued that source memory plays such an important role in communication because it allows speakers to effectively modulate their conversational commitments and thereby greatly expand their communicative competencies.…”
Section: The Role Of Source Claims In Communicationmentioning
confidence: 99%
“…Senior physicians, despite having higher knowledge, could not motivate junior physicians, nurses, pharmacists to improve their knowledge and practice. Despite their Decades of research has shown that people have the capacity to voluntarily forget things, so to keep things in mind, reminders of information are needed [42]. Reading the authentic source of information is also essential to obtain the correct information so that the government and hospital policymakers should guide the recommended sources of information such as the WHO and the Center for Disease Control (CDC) guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Thus even Fernández (2019) , who rejects the causal theory, builds a representation of a causal link between the present representation and the past experience into the content of the memory in an attempt to account for the phenomenology of remembering. Similarly, Mahr and Csibra (2018 , 2020) , we have seen, argue that memory is able to perform its communicative function because its phenomenology indicates to the rememberer the existence of a causal relationship between his memory and his experience of the corresponding event—episodic memory is able to serve as a “witness trump card” ( Henry and Craver, 2018 ) because its phenomenology includes causality (“I remember this because I saw it happen”), as opposed to mere actuality (“This happened”). Accordingly, we will take it for granted, in what follows, that the phenomenology of remembering includes the causation component, as well as the pastness and self components.…”
Section: Introducing the Feeling View Of Episodic Phenomenologymentioning
confidence: 91%